Anti-inflammatory activity of electron-deficient organometallics. Issue 11 (29th November 2017) - Zhang, Jingwen; Pitto-Barry, Anaïs; Shang, Lijun; Barry, Nicolas P. E.
Abstract : We report an evaluation of the cytotoxicity of a series of electron-deficient (16-electron) half-sandwich precious metal complexes of ruthenium, osmium and iridium ([Os/Ru( η 6 - p -cymene)(1, 2-dicarba- closo -dodecarborane-1, 2-dithiolato)] (1/2 ), [Ir( η 5 -pentamethylcyclopentadiene)(1, 2-dicarba- closo -dodecarborane-1, 2-dithiolato)] (3 ), [Os/Ru( η 6 - p -cymene)(benzene-1, 2-dithiolato)] (4/5 ) and [Ir( η 5 -pentamethylcyclopentadiene)(benzene-1, 2-dithiolato)] (6 )) towards RAW 264.7 murine macrophages and MRC-5 fibroblast cells. Complexes 3 and 6 were found to be non-cytotoxic. The anti-inflammatory activity of 1–6 was evaluated in both cell lines after nitric oxide (NO) production and inflammation response induced by bacterial endotoxin lipopolysaccharide (LPS) as the stimulus. All metal complexes were shown to exhibit dose-dependent inhibitory effects on LPS-induced NO production on both cell lines. Remarkably, the two iridium complexes 3 and 6 trigger a full anti-inflammatory response against LPS-induced NO production, which opens up new avenues for the development of non-cytotoxic anti-inflammatory drug candidates with distinct structures and solution chemistry from that of organic drugs, and as such with potential novel mechanisms of action.